2016
DOI: 10.1002/stem.2457
|View full text |Cite
|
Sign up to set email alerts
|

Liver Progenitors Isolated from Adult Healthy Mouse Liver Efficiently Differentiate to Functional Hepatocytes In Vitro and Repopulate Liver Tissue

Abstract: It has been proposed that tissue stem cells supply multiple epithelial cells in mature tissues and organs. However, it is unclear whether tissue stem cells generally contribute to cellular turnover in normal healthy organs. Here, we show that liver progenitors distinct from bipotent liver stem/progenitor cells (LPCs) persistently exist in mouse livers and potentially contribute to tissue maintenance. We found that, in addition to LPCs isolated as EpCAM cells, liver progenitors were enriched in CD45 TER119 CD31… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
27
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 37 publications
1
27
0
1
Order By: Relevance
“…Sox9 + periportal hepatocytes were also identified as hepatocyte progenitors during regeneration from chronic liver injury39. Furthermore, we showed that small mononuclear hepatocyte progenitors existed in the ICAM-1 + fractions isolated from healthy adult mouse livers34. The ICAM + HNF4α + mononuclear cells did not specifically localize in liver lobules and showed a low expression of both Axin2 and Lgr5 genes.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…Sox9 + periportal hepatocytes were also identified as hepatocyte progenitors during regeneration from chronic liver injury39. Furthermore, we showed that small mononuclear hepatocyte progenitors existed in the ICAM-1 + fractions isolated from healthy adult mouse livers34. The ICAM + HNF4α + mononuclear cells did not specifically localize in liver lobules and showed a low expression of both Axin2 and Lgr5 genes.…”
Section: Discussionmentioning
confidence: 85%
“…To our knowledge, a clone derived from human hepatocyte has never been generated without gene transfection. Notably, we recently reported that clones of SHs isolated from a healthy adult mouse liver were established, and these clones retain the potential to differentiate into MHs in vitro and in vivo 34. These findings indicate that differences in self-renewal potential exist between animals.…”
Section: Discussionmentioning
confidence: 85%
“…Recent evidences indicate that LPCs isolated from adult healthy mouse liver are important source of new mature hepatocytes for tissue maintenance and repair in vivo, and for regenerative medicine ex vivo [26,27]. Understanding the mechanism that LPCs differentiation into hepatocytes may allow for novel induction strategies for chronic liver disease [28].…”
Section: Discussionmentioning
confidence: 99%
“…Hepatic oval cells display a distinct phenotype and have been shown to be a bipotential progenitor of two types of epithelial cells found in the liver, hepatocytes and bile ductular cells. HOC act as facultative hepatic stem cells (HSCs) that differentiate into hepatocytes and cholangiocytes in severely injured liver [119]. Oval cells constitute an interesting hepatic cell population.…”
Section: Liver Oval Cellsmentioning
confidence: 99%
“…EpCAM+ cells isolated from injured liver proliferate to form colonies in vitro, and the clonally expanded cells differentiate into hepatocytes and cholangiocytes. More often, proliferating mouse oval cells represent transit-amplifying cells rather than HSCs [119]. Hepatic oval cell activation, proliferation, and differentiation are also regulated by physiological conditions during severe hepatic injury [124] (Figure 5).…”
Section: Liver Oval Cellsmentioning
confidence: 99%